MENINGKATKAN KEMAMPUAN BERBICARA SISWA KELAS III SDN 108/IX TANJUNG PAUH MENGGUNAKAN MODEL GAMBAR - Eti Kusuma; Puput Wahyu Hidayat (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to describe the improvement of speaking ability among third-grade students at SDN 108/IX Tanjung Pauh and the effectiveness of the picture model (Picture and Picture) in the learning process. The study is grounded in initial observation data showing that of 18 third-grade students, only 4 students (22%) were able to speak well when asked questions by the teacher, while the remaining 14 students (78%) had not yet been able to speak fluently, clearly, and with appropriate vocabulary and intonation. This low speaking ability is attributed to external factors, namely the habit of using the local language at home, and internal factors such as the limited use of varied media and learning models, which made students passive and reluctant to speak in front of the class. This study employs a Classroom Action Research (CAR) design implemented across three cycles, each consisting of planning, acting, observing, and reflecting stages, applying the syntax of the picture model: conveying learning objectives, presenting material, displaying randomized pictures, having students arrange the pictures logically, students' oral expression, and concept reinforcement by the teacher. Data were gathered through observation sheets, oral performance tests using a rubric covering articulation, fluency, vocabulary, and intonation, and documentation. A review of relevant prior studies indicates that the application of the picture model has consistently improved elementary students' speaking ability across cycles. These findings are expected to serve as a reference for teachers in selecting appropriate learning models to improve the speaking ability of lower-grade students.